2021
DOI: 10.1371/journal.pone.0246950
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary phosphates from organic and inorganic sources on parameters of phosphorus homeostasis in healthy adult dogs

Abstract: Background The impact of dietary phosphorus (P) excess, especially on renal and cardiovascular health, has been investigated in several species, but little is known in dogs. Objective The aim of this study was to examine effects of different P sources on concentration and postprandial kinetics of selected parameters of P homeostasis in dogs. Methods Eight beagles received one control diet (P 0.5% dry matter [DM]) and three high P diets (poultry meal, NaH2PO4, and KH2PO4; P 1.7% DM) for 18d. Urine samples w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 94 publications
0
15
0
5
Order By: Relevance
“…Hierbei wird gemessen, wie viel Phosphor sich jeweils nach 1 Minute oder nach 90 Minuten in Wasser oder einer schwach sauren Lösung (0,4 % HCl) löst. Der Fokus lag auf der hochlöslichen Fraktion (Phosphor löslich nach 1 Minute in Wasser; P sol1 ), da dieser Anteil für die Effekte auf die Phosphor-und Kalziumhomöostase maßgeblich verantwortlich gemacht wird [32]. Um die Vergleichbarkeit der Ergebnisse zu optimieren, wurden die jeweiligen Phosphorgehalte auf die umsetzbare Energie (metabolisable energy; ME) in den Futtermitteln bezogen, die anhand der deklarierten Rohnährstoffgehalte abgeschätzt wurde (EU Standard EN16967:2017).…”
Section: Phosphorbestimmung Und Datenauswertungunclassified
See 1 more Smart Citation
“…Hierbei wird gemessen, wie viel Phosphor sich jeweils nach 1 Minute oder nach 90 Minuten in Wasser oder einer schwach sauren Lösung (0,4 % HCl) löst. Der Fokus lag auf der hochlöslichen Fraktion (Phosphor löslich nach 1 Minute in Wasser; P sol1 ), da dieser Anteil für die Effekte auf die Phosphor-und Kalziumhomöostase maßgeblich verantwortlich gemacht wird [32]. Um die Vergleichbarkeit der Ergebnisse zu optimieren, wurden die jeweiligen Phosphorgehalte auf die umsetzbare Energie (metabolisable energy; ME) in den Futtermitteln bezogen, die anhand der deklarierten Rohnährstoffgehalte abgeschätzt wurde (EU Standard EN16967:2017).…”
Section: Phosphorbestimmung Und Datenauswertungunclassified
“…[31][32], ist der Körper gezwungen, die Phosphatlast schnell und effizient zu reduzieren. Vermittelt durch Parathormon, FGF23, Klothoprotein und andere Mediatoren erhöht sich somit die Menge an renal ausgeschiedenem Phosphor und damit die Phosphormenge pro Nephron.…”
unclassified
“…Although the implications of high dietary P is not fully researched and understood, it has been reported that beagles who were orally administered 0.8 g/kg BW dipotassium phosphate (K 2 HPO 4 ) developed renal damage with accompanying clinical symptoms [ 75 ], which underlines source as well as dietary level as additional important factors. Differences in P digestibility and post-prandial serum P and PTH have been demonstrated in adult beagle dogs in response to dietary P derived from different sources [ 50 , 76 ], as has also been found in adult cats [ 29 , 49 , 77 ]. Whilst these studies showing post-prandial responses provide valuable insights of differing bioavailability and absorption properties from different P sources, it does not provide conclusive evidence of possible health consequences or any protective mechanisms that species and breeds have to eliminate surplus P.…”
Section: Discussionmentioning
confidence: 96%
“…Organic acids such as phosphoric acid, citric acid, tartaric acid, fumaric acid, lactic acid, acetic acid, and formic acid have also been used in the past to improve the palatability of pet foods [43]. Phosphates, pyrophosphates, and polyphosphates have also been explored as potential palatants in dry pet foods [44], although there are some concerns regarding their long-term effects on renal functions of pets [45][46][47]. Such palatants could be added either as an ingredient during a mixing process or as a surface coating after product processing.…”
Section: Overview Of Palatants Used In Dry Pet Foodsmentioning
confidence: 99%